Peran United Nations High Commissioner For Refugees (UNHCR) dalam Menangani Permasalahan Stateless di malaysia - Pristina Widya; Najamuddin Khairur Rijal (Pencerah Publishing, 2022)
This study discusses the role of the United Nations High Commissioner for Refugees (UNHCR) in dealing with stateless problems in Malaysia from 2014-2017. As an international organization, UNHCR deals with stateless issues, namely people who are not considered citizens by any country according to their legal operations. The research method used is descriptive-qualitative. The results found that UNHCR performed its role as an information provider, law enforcer, and policy implementer. As an information provider, UNHCR carries out the #Ibelong campaign and provides information about its partners. As a rule enforcer, UNHCR encourages Malaysia to ratify the stateless convention and provide legal assistance. As a policy implementer, UNHCR carries out mapping projects and provides funding for stateless programs.